Optimization design of high-speed data acquisition system based on DMA double cache mechanism. (November 2022) - Zhou, Weina; Yang, Shuang
Abstract: The large-capacity on-chip cache often causes timing problems or erroneous transmission in the high-speed acquisition of massive data. However, many factors always affect the communication performance of the system. In this paper, a high-speed data acquisition system (DAS) based on DMA double cache mechanism is introduced. Aurora protocol is used for optical fiber transmission, and the line rate dynamic adaptive design of the X1 channel is realized. In the SDRAM controller, the DMA dual channel is targeted optimized, including memory ping-pong operation and channel arbiter. In addition, collecting data from the lower computer or transmitting data to the upper computer are both based on software instructions in our design, which is more flexible and stable than receiving data without instructions. Finally, to optimize the transmission process of cached data, we cascaded FIFOs in different modules. The results show that the system can receive optical fiber data at the rate of 7.57Gbps, and the average DMA communication efficiency reaches 76.9%.